In silico screening of potential drug with antileishmanial activity and validation of their activity by in vitro and in vivo studies (2015)
ABSTRACT: The research on discovery and development of new treatments for cutaneous leishmaniasis has been declared as priority. Using bioinformatics approaches, this study aimed to identify antileishmanial activity in drugs that are currently used as anti-inflammatory andwound healing by such anti-Leishmania activity was validated by in vitro and in vivo assays. In silico analysis identified 153 compounds from which 87 were selected by data mining of DrugBank database, 22 and 44 were detected by PASS (www.way2drug.com/passonline) and BLAST (http://blast.ncbi.nlm.nih. gov/) alignment, respectively. The majority of identified drugs are used as skin protector, anti-acne, anti-ulcerative (wound healer) or anti-inflammatory and few of them had specific antileishmanial activity. The efficacy as antileishmanial was validated in vitro in 12/23 tested compounds and in all seven compounds that were evaluated in in vivo assays. Notably, this is the first report of antileishmanial activity for adapalene. In conclusion, bioinformatics tools not only can help to reduce time and cost of the drug discovery process but also may increase the chance that candidates identified in silico which have a validated antileishmanial activity by combining different biological properties.